Antimicrobial Resistance in Escherichia coli from the Broiler Farm Environment, with Detection of SHV-12-Producing Isolates - Sandra Martínez-Álvarez; Susana Sanz; Carmen Olarte; Raquel Hidalgo-Sanz; Isabel Carvalho; Rosa Fernández-Fernández; Allelen Campaña-Burguet; Javier Latorre-Fernández; Myriam Zarazaga; Carmen Torres (MDPI AG, 2022)
Antimicrobial resistance is an important One Health challenge that encompasses the human, animal, and environmental fields. A total of 111 Escherichia coli isolates previously recovered from manure (n = 57) and indoor air (n = 54) samples from a broiler farm were analyzed to determine their phenotypes and genotypes of antimicrobial resistance and integron characterization; in addition, plasmid replicon analysis and molecular typing were performed in extended-spectrum-beta-lactamase (ESBL) producer isolates. A multidrug-resistance phenotype was detected in 46.8% of the isolates, and the highest rates of resistance were found for ampicillin, trimethoprim-sulfamethoxazole, and tetracycline (>40%); moreover, 15 isolates (13.5%) showed susceptibility to all tested antibiotics. None of the isolates showed imipenem and/or cefoxitin resistance. Twenty-three of the one hundred and eleven E. coli isolates (20.7%) were ESBL producers and carried the blaSHV-12 gene; one of these isolates was recovered from the air, and the remaining 22 were from manure samples. Most of ESBL-positive isolates carried the cmlA (n = 23), tet(A) (n = 19), and aac(6')-Ib-cr (n = 11) genes. The following genetic lineages were identified among the ESBL-producing isolates (sequence type-phylogroup-clonotype): ST770-E-CH116-552 (n = 12), ST117-B2-CH45-97 (n = 4), ST68-E-CH26-382/49 (n = 3), ST68-E-CH26-49 (n = 1), and ST10992-A/B1-CH11-23/41/580 (n = 4); the latter two were detected for the first time in the poultry sector. At least two plasmid replicon types were detected in the ESBL-producing E. coli isolates, with IncF, IncF1B, IncK, and IncHI1 being the most frequently found. The following antimicrobial resistance genes were identified among the non-ESBL-producing isolates (number of isolates): blaTEM (58), aac(6')-Ib-cr (6), qnrS (2), aac(3)-II (2), cmlA (6), tet(A)/tet(B) (22), and sul1/2/3 (51). Four different gene-cassette arrays were detected in the variable region of class 1 (dfrA1-aadA1, dfrA12-aadA2, and dfrA12-orf-aadA2-cmlA) and class 2 integrons (sat2-aadA1-orfX). This work reveals the worrying presence of antimicrobial-resistant E. coli in the broiler farm environment, with ESBL-producing isolates of SHV-12 type being extensively disseminated.